Pengaruh Organizational Justice terhadap Organizational Commitment pada Karyawan PT X - Wahyu Anggoro; Maya Rosmayati Ardiwinata; Nurul Yanuarti (Universitas Muhammadiyah Jember, 2020)
PT X aims its vision to become a World Class Life Science Company with Global Competitiveness. In order to support that vision, PT X needs its employees to be committed to contribute in achieving said vision. This research aims to investigate the effect of Organizational Justice to Organizational Commitment among the employees of PT X using linear regression statistical analysis. The research was done to 550 employees on the level of Heads of Department all the way to the Operators using supervised self-report questionnaires. Data collection was done by deploying Organizational Justice questionnaire, developed from the Justice Questionnaire by Colquitt et al., and Organizational Commitment questionnaire based on the questionnaire by Allen Meyer. Research result indicates significant effect of Organizational Justice towards Affective (R=0,436, p0,001), Continuance (R=0,087, p0,001), and Normative (R=0,411, p0,001) Commitment.